2015
DOI: 10.18433/j3j88q
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Peroral Delivery of Insulin via Vitamin B12 Modified Trimethyl Chitosan Nanoparticles

Abstract: ABSTRACT-PURPOSE:We investigated the effect of vitamin B12 (VB12) modification on the insulin absorption from trimethyl chitosan(TMC) nanoparticles (NPs) under the influence of mucus. METHODS: TMC and TMC-VB12 were synthesized and insulin loaded TMC/TMC-VB12 nanoparticles were prepared and characterized. Modified and unmodified nanoparticles were studied with Caco-2/HT29-MTX cell model and ligated rat ileum loop. RESULTS: Compared with unmodified NPs, VB12 modified NPs showed significantly higher drug internal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 41 publications
0
12
0
Order By: Relevance
“…Francis et al [ 27 ] reported that oral absorption and delivery efficiency of polymeric micelles were substantially enhanced by linkage to VB12 and that the process is initiated by the complexation of VB12 with IF. Ke et al [ 28 ] showed that VB12 modified nanoparticles significantly improved the drug internalization and the transport efficacy through cell monolayer. According to these findings, we designed and synthesized the Chit-DC-VB12 nanoparticles, while the FTIR, 1 H NMR and UV–Vis analyses confirmed that the deoxycholic acid residues and vitamin B12 residues were conjugated with the chitosan chains and their DS values were 3 and 0.3%, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Francis et al [ 27 ] reported that oral absorption and delivery efficiency of polymeric micelles were substantially enhanced by linkage to VB12 and that the process is initiated by the complexation of VB12 with IF. Ke et al [ 28 ] showed that VB12 modified nanoparticles significantly improved the drug internalization and the transport efficacy through cell monolayer. According to these findings, we designed and synthesized the Chit-DC-VB12 nanoparticles, while the FTIR, 1 H NMR and UV–Vis analyses confirmed that the deoxycholic acid residues and vitamin B12 residues were conjugated with the chitosan chains and their DS values were 3 and 0.3%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Upon reaching the small intestine, this complex binds to IF receptors located in the luminal surface of the intestine, facilitating the transport across intestinal epithelium by receptor-mediated endocytosis. In previous works [ 28 ], after modified by VB12, nanoparticles showed significantly higher drug internalization in cell model than unmodified nanoparticles, and an increased transportation of insulin. However, no such report is available where this concept has been used for oral delivery of scutellarin.…”
Section: Introductionmentioning
confidence: 96%
“…However, a membrane filter simply covered by the mucus layer can generate a comparison of the penetration of compounds without the existence of an epithelial barrier and can be used to evaluate the diffusion of different substances through the mucus layer [26–29]. A study used the Caco‐2/HT29‐MTX coculture cell model to evaluate the transcellular permeation of nanoparticles by virtue of not only the presence of the mucus layer but also a TEER value that was close to that of the intestinal epithelium [30]. The results indicated the ability of tight junctions to open epithelial cells, which plays a key role in the paracellular route of drug transport.…”
Section: Simulating the Gastrointestinal Mucus Barriermentioning
confidence: 99%
“…Lyophilised nanoparticles can be absorbed by different mechanisms including endocytotic pathway and paracellular pathway in the GI tract (15,49,(72)(73)(74)(75)(76). In terms of endocytic pathway, as ligand conjugation was not manipulated in the developed nanoparticles, the nanoparticles can only be adsorbed to the GI cells by unspecific electrostatic forces (adsorptive endocytosis), but not active targeting to GI receptors (receptor-mediated endocytosis).…”
Section: In Vitro Cellular Studies Of Absorption Mechanism Of Nanoparticlesmentioning
confidence: 99%